ANALISIS PENGEMBANGAN PRODUK VIRGIN COCONUT OIL (VCO) SEBAGAI INOVASI LOKAL BERDAYA SAING DI DESA AIMOLI KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Ester Prity Claudia Biri; Paulus Ayub Animau; Novita Yuliana Wabang; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
In Aimoli Village, North West Alor District, Alor Regency, there is a community-managed MSME called Ma Netha. This is a local production unit that develops various herbal products such as candlenut oil, virgin coconut oil (VCO), and red ginger powder. These products are produced using abundant local raw materials and modernized traditional processing techniques. This study aims to analyze the herbal product development strategy implemented by Ma Netha and identify factors that support product competitiveness at the local level. The method used was a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The results indicate that product innovation, raw material quality, and hygienic production processes are key factors in increasing product sales value. Furthermore, local community support, raw material availability, and production skills strengthen Ma Netha's position as a competitive herbal producer. This study confirms that developing herbal products based on regional potential can be an effective strategy for increasing the economic independence of rural communities.